Studi Penggunaan Antibiotik pada Pasien Penyakit ISPA Usia Bawah Lima Tahun di Instalasi Rawat Jalan Puskesmas Sumbersari Periode 1 Januari-31 Maret 2014 (Study of Antibiotics Use on ARI Patients in Under Five Years Outpatient Clinic, Sumbersari Health - Tika Sugiarti; Arya Sidemen; Wiratmo Wiratmo (Pustaka Kesehatan, 2015)
Acute respiratory tract infections (ARI) disease often occurs on children. The episode of cough and cold disease on toddlers in Indonesia is estimated to be 3 to 6 times each year. The high prevalence of respiratory disease and its effect have brought the high consumption of free drugs and antibiotics. This study aimed to determine the profile of the patients, the treatment of respiratory diseases, antibiotic usage patterns and congruence with of the standards of Indonesian Health Ministry in 2012 based on the exact parameters indication, the right type, and the right dosage. The results showed that the amount of male patients (53%) were more than the amount of female patients and the largest age group in ARI patients were ages 13-24 months (30%). Drugs given to patients consist of two kinds, namely antibiotics and supportive therapy drugs. Antibiotic therapy given in ARI was amoxicillin and co-trimoxazole. Syrup is dosage form mostly used. Based on compliance with the standards of Indonesian Health Ministry in 2012, can be concluded that the use of antibiotics were 24.2% exact indication, 100% right type, and 8.9% correct dose. Keywords: acute respiratory tract infections (ARI), toddler, antibiotic, standards of Indonesian Health Ministry in 2012